Evaluation of general dentists' perspectives on periodontal surgery (Annals of Medical Research, 2024)
Aim: Periodontal treatments are a very important part of general dentistry. This study aimed to evaluate general dentists' perspectives on surgical and non-surgical periodontal treatments and to examine the decision criteria of these dentists to refer their patients to a periodontist.Materials and Methods: The survey used in this study consisted of 28 questions and was delivered to general dentists online. The survey primarily asks dentists about their gender, age, information about the institution they work in, and years of professional experience. Other questions in the survey include topics related to periodontal examination, referral to a periodontist for phase 1 periodontal treatment, referral for periodontal surgical treatment, surgical treatments applied and their frequency, and periodontal surgical treatment procedures.Results: A total of 171 general dentists (85-male, 86-female) with an average age of 34±10 answered the survey questions. The rate of participants who stated that they performed the phase 1 periodontal treatment of their patients themselves was 77.8%, while the rate of those who performed the surgical periodontal treatment themselves was 20.5%. No statistically significant relationships were obtained between the participants' gender, the institution they work in, and their responses regarding periodontal diagnosis and treatments. (p>0.05) The rates of performing a periodontal examination and obtaining a periodontal index in the first session are 70.1% and 38.0% for dentists working in private practice, while they are 44.1% and 14.7% for dentists working in a public hospital. In addition, it has been determined that all physicians who perform surgical treatments themselves work in private practice (p
Keywords: Dentist; Periodontitis; Oral surgical procedures